Predictive effect of perceived social support and selfdisclosure on digital game addiction in young adults - Saylan, Ezgi; Çolak, Recep (Journal of Dependence, 2023)
Objective: This study aims to examine the predictive roles of perceived social support and self-disclosure on digital game addiction in young adults. Method: The participants of this research, which is structured according to the relational survey model, consist of 382 young adult individuals. Participants were selected by a convenient sampling method. Personal Information Form, Digital Game Addiction Scale, Self-Disclosure Scale, and Multidimensional Perceived Social Support Scale were used as data collection tools in the study. Result: The predictive model explained 58% of the variance in digital game addiction. In addition, as a result of the analysis, the amount of self-disclosure (β = -.08, p<.01) was a negative predictor of digital game addiction, and control (β = .77, p<.01) was a positive predictor of digital game addiction; perceived support from family (β = .01, p>.05), perceived support from friends (β = -.05, p>.05), perceived support from special person (β = .04, p>.05), intention (β = .04, p>.05), positivity (β = .05, p>.05) and honesty (β = .02, p>.05) sub-dimensions were not found to be significant predictors of digital game addiction. Conclusion: The increase in perceived social support did not affect digital game addiction. As another result, considering that the increase in self-disclosure behavior has a reducing effect on digital game addiction, self-disclosure behavior can be considered one of the protective factors in digital game addiction.